Charcot-Marie-Tooth disease: from historical landmarks in Brazil to current care perspectives - Cavalcanti, Eduardo Boiteux Uchôa; Leal, Rita de Cássia Carvalho; Marques Junior, Wilson; Nascimento, Osvaldo José Moreira do (Arquivos de Neuro-Psiquiatria, 2023)
Hereditary motor and sensory neuropathy, also known as Charcot-Marie-Tooth disease (CMT), traditionally refers to a group of genetic disorders in which neuropathy is the main or sole feature. Its prevalence varies according to different populations studied, with an estimate between 1:2,500 to 1:10,000. Since the identification of PMP22 gene duplication on chromosome 17 by Vance et al., in 1989, more than 100 genes have been related to this group of disorders, and we have seen advances in the care of patients, with identification of associated conditions and better supportive treatments, including clinical and surgical interventions. Also, with discoveries in the field of genetics, including RNA interference and gene editing techniques, new treatment perspectives begin to emerge. In the present work, we report the most import landmarks regarding CMT research in Brazil and provide a comprehensive review on topics such as frequency of different genes associated with CMT in our population, prevalence of pain, impact on pregnancy, respiratory features, and development of new therapies.
Keywords: Charcot-Marie-Tooth disease; Hereditary Sensory and Motor Neuropathy; Peripheral Nervous System diseases